The Influence of Nudges on Workers’ Safety Behavior in the Construction Industry - Tzu-Lien Tzou; Pin-Chan Lee; Tzu-Ping Lo (Engineering Proceedings)
The nudge theory has been applied to improve safety behavior in various industries. We implemented the nudge theory in the construction industry to improve worker safety. Nudges for construction safety were grouped into three categories and used in a project. The application of nudges improved workers’ safety behavior, particularly in highlighting control measures. The background analysis results reveal that the implementation of nudges did not vary by gender, nationality, or age, demonstrating its high universality. The results of this study offer a reference for stakeholders in the construction industry who are aiming to bolster worker safety.